The Biblical Concept of Holiness - Roman Krawczyk (Ruch Biblijny i Liturgiczny, 2014)
The concept of holiness is a highly complex area connected with God’s mystery in particular, but also referring to worship, morality, objects and space. In this article, the author analyses the Old and New Testaments texts and also extends the biblical image of holiness by the views included in the Dead Sea Scrolls and rabbinic theology. The study is ended in conclusions drawn from the research.